2020
DOI: 10.21608/tsnj.2020.107688
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Implementation Management program about Infection Control practices for Nursing Staff

Abstract: Back ground: Management program about infection control is important to help head nurses gain knowledge to perform their roles, and for nurses to comply with standard infection control measures. Objective: Evaluate efficacy of implementing management program about infection control practices for nursing staff. Setting: All departments in Tanta University Emergency Hospital. Subjects: All head nurses (N= 31) and nurses (N =175) working in all departments of emergency hospital. Tools: (1) Infection Control Knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Furthermore, Desnita and Surya (2020) conducted a study in which the results showed that infection control performance was significantly higher in the peer mentoring group. This was also, similarly, to a study made by Marey et al (2020) which revealed that there was a high statistically significant improvement in nurses' levels of total performance in all items of infection control post peer mentoring program.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, Desnita and Surya (2020) conducted a study in which the results showed that infection control performance was significantly higher in the peer mentoring group. This was also, similarly, to a study made by Marey et al (2020) which revealed that there was a high statistically significant improvement in nurses' levels of total performance in all items of infection control post peer mentoring program.…”
Section: Discussionsupporting
confidence: 81%
“…The results of this study also verified that a great improvement is found regarding the studied nurses' total score level of practices of infection control standards pre, immediately and one month post program implementation. These findings are in the same vein with Marey, Shabaan and Abo Gad (2020) [31] who concluded that pre-program majority (90.3%) of head nurses had mild level of performance of educational , consultation, research and support team in surveillance roles decreased to (3.2%) post program. Nurses range (15.4% -22.9%) showed compliance level to infection control practices pre-program, improved to range (75.4% -84.0%) post program with highly statistically significant differences (p= < 0.001).…”
Section: Discussionsupporting
confidence: 78%
“…According to the results of a research done in Egypt by EL-Shafey, El-Dakhakhny, and Mohammed (2019) [30] , the majority of participants had a nursing school certificate but had never attended any training on infection control procedures. Additionally, Marey, Shabaan and Abo Gad (2020) [31] found, three quarters of the study participants were married, and two-thirds of them never attended an infection control training session.…”
Section: Discussionmentioning
confidence: 90%
“…The tool contained (21) questions with (21) total scores of the questionnaire. Knowledge obtained from the studied nurses was checked with a model key answer, (1) grade was given for the correct answers, and (zero) grades were given for incorrect answers.…”
Section: Scoring Systemmentioning
confidence: 99%